The Role of Metabolic Syndrome in The Nature of Postinfarction Remodeling of The Heart in Patients with Chronic Heart Failure (Texas Journal of Medical Science, 2023)
The aim is to study of heart’s structure and hemodynamic indicators according to composition of metabolic syndrome components in the patient with chronic heart failure (CHF)functional class (FC) IIIII. 62 men-patient with cardiosclerosis after heart attack were examined by the way of echocardiography on CHF FC II-III (NYHA). According to metabolic syndrome components they are devided into 3 groups: 1 st group (n=20), patients without signs of metabolic syndrome; 2nd group (n=21) patients with combination of dyslipidemia (DLP), abdominal obesity (AO), arterial hypertenion (AG) and hypertriglyceridemia; 3rd group (n=21) with different combination of dyslipoproteinemia, diabetes and obesity also AG and hypertriglyceridemia. in CHF passed with metabolic syndrome is seen a clear sign of heart’s systolic and diastolic.the presence of metabolic syndrome in CHF also its progressing is the subject to be hypertrophy of left ventricle, breaking the transmitral blood flow, also thickening of barier between ventricles and left ventricle back thickness